Movement analysis for javelin throwers in the Qatar 2009 championships - Mahmud, E. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
A biomechanical analysis of the javelin throw at the Qatar Athletics Championships in Doha with comparison to international throwers was carried out by the Qatar Olympic Committee in 2009. This paper presents the results of this study for male finalists. The methodology used is based on Video Photogrammetric analyses at 50Hz. The results show the characteristics of the throwers' individual model at the event, which for practical purposes can be compared with the performance of the same throwers in other competitions. In general the Qatari throwers held the javelin longer and threw at a lower. Variations in throwers' technique may result in differences in performance.